2011
DOI: 10.1021/bi200409a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Mononitrosyl Complexes in Heme–Nonheme Diiron Centers within the Myoglobin Scaffold (FeBMbs): Relevance to Denitrifying NO Reductase

Abstract: Denitrifying NO reductases are evolutionarily related to the superfamily of heme-copper terminal oxidases. These transmembrane protein complexes utilize a heme-nonheme diiron center to reduce two NO molecules to N2O. To understand this reaction, the diiron site has been modeled using sperm whale myoglobin as a scaffold and mutating distal residues Leu-29 and Phe-43 to histidines, and Val-68 to a glutamic acid to create a nonheme FeB site. The impact of incorporation of metal ions at this engineered site on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…Besides inorganic model compounds [32] (and references therein), an engineered sperm whale myoglobin was constructed [33,34]. It successfully reproduced the NOR active centre with the magnetic coupling between the two iron sites, but experiments carried out in the presence of NO have shown low reductase activity [33][34][35]. Recently, Resonance Raman Spectroscopy was used to investigate the NO reduction mechanism in these modified myoglobins, and the formation of a stable heme-NO complex as a reaction intermediate was pointed.…”
Section: Introductionmentioning
confidence: 99%
“…Besides inorganic model compounds [32] (and references therein), an engineered sperm whale myoglobin was constructed [33,34]. It successfully reproduced the NOR active centre with the magnetic coupling between the two iron sites, but experiments carried out in the presence of NO have shown low reductase activity [33][34][35]. Recently, Resonance Raman Spectroscopy was used to investigate the NO reduction mechanism in these modified myoglobins, and the formation of a stable heme-NO complex as a reaction intermediate was pointed.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In bioengineered non-heme/heme NOR, the O NO atom of heme-NO electrostatically interacts with adistal metal ion, such as Zn 2+ or Fe 2+ ,inthe non-heme pocket, which also decreases the n NO value up to 50 cm À1 . [20] As DFT calculations on heme-copper oxidoreductase showed that the NO reduction proceeds through an NÀN coupling phase facilitated by the protonation of heme-NO to form an HN 2 O 2 À intermediate,w ep ostulated that treatment with CD 3 OD induced the formation of 2···CD 3 OD (shifted to n NO = 1513 cm À1 )t hrough Hbonding.I ti st his polarization that stimulates the interaction between 2 and 2···CD 3 OD and allows NÀNcoupling to proceed and form aplausible [N 2 O 2 ]bridged intermediate.…”
mentioning
confidence: 99%
“…(17) In addition, we found that equally low N-O stretching frequencies are observed when their Fe B sites are occupied with either Fe(II) or Zn(II), but not with Cu(I), suggesting that the 6cLS heme nitroxyl-like complexes are stabilized by electrostatic interactions with the divalent metal center at their Fe B sites. (17)…”
mentioning
confidence: 80%